1993
DOI: 10.1073/pnas.90.23.11024
|View full text |Cite
|
Sign up to set email alerts
|

A difference Fourier-transform infrared study of two redox-active tyrosine residues in photosystem II.

Abstract: Photosystem II, the photosynthetic wateroxidizing complex, contains two redox-active tyrosine residues.Although current models suggest that these tyrosines are located in symmetric positions in the reaction center, there are functional differences between them. To elucidate those structural factors that give rise to this functional asymmetry, we have used difference Fourier-transform infrared spectroscopy to obtain the vibrational difference spectrum associated with the oxidation of each of these redox-active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 41 publications
12
61
3
Order By: Relevance
“…We attribute the 1,483-cm Ϫ1 amplitude increase to a contribution from Y Z ⅐ in these OEC-inactivated samples. This Y Z ⅐ assignment is in agreement with the previous assignments of MacDonald et al (27), which were derived from analysis of the photoaccumulated Y Z ⅐ spectrum and have been supported by additional studies (reviewed in refs. 28 and 29).…”
Section: Resultssupporting
confidence: 92%
“…We attribute the 1,483-cm Ϫ1 amplitude increase to a contribution from Y Z ⅐ in these OEC-inactivated samples. This Y Z ⅐ assignment is in agreement with the previous assignments of MacDonald et al (27), which were derived from analysis of the photoaccumulated Y Z ⅐ spectrum and have been supported by additional studies (reviewed in refs. 28 and 29).…”
Section: Resultssupporting
confidence: 92%
“…The photooxidation of P700 has been previously investigated at ambient temperature in the 1800 to 1200 cm -1 spectral range in pea thylakoids and the corresponding PS I-enriched particles (Tavitian et al 1986), in thylakoids of the cyanobacterium Spirulina geitleiri (Tavitian 1987;Nabedryk et al 1990a) as well as at -10 °C on a PSI particle from the cyanobacterium Synechocystis (MacDonald et al 1993). The data obtained from these different PSI particles are in good agreement.…”
Section: Introductionsupporting
confidence: 68%
“…Based on radical cation studies of Chl a and pyroChl a, the 1717/1700 cm -l signal previously observed at room temperature in P700+/P700 spectra has been assigned to a frequency upshift upon P700 photooxidation of the free 9-keto C=O group(s) of the Chl a molecule(s) constituting P700 (Tavitian et al 1986;Nabedryk et al 1990a). For Synechocystis PSI particles, a corresponding signal is found at 1717/1697 cm -1 at both low ( Figure 2a) and ambient temperature (data not shown, see also MacDonald et al 1993). This signal could arise from only one or from two Chl molecules, provided the 9-keto C=O of these two Chls absorb at the same frequency.…”
Section: Comparison Between the Primary Donor In Psi And In The Hetermentioning
confidence: 79%
“…A methodology to obtain double-difference FT-IR spectra reflecting contributions from D•ϪD has been reported (24). By using 90-and 4-min dark adaptations, two light-minusdark difference spectra, ref lecting D•Z•ϪDZ and D•Z•ϪD•Z, are produced.…”
Section: Resultsmentioning
confidence: 99%
“…To observe the proton acceptor for tyrosine D• directly, we have used difference Fourier-transform infrared (FT-IR) spectroscopy (24). Because the oxidation of D is light-induced (25), a doubledifference spectrum, reflecting D• -D, can be acquired, as previously described.…”
mentioning
confidence: 99%